Premature ejaculation: An investigative study into assumptions, facts and perceptions of patients from the Middle East (PEAP STUDY). Issue 3 (3rd July 2021) - Albakr, Ahmad; Arafa, Mohamed; Elbardisi, Haitham; ElSaid, Sami; Majzoub, Ahmad
ABSTRACT: Objective: To determine the prevalence of premature ejaculation (PE) in Qatar as a representative of the Middle East region and the population perception of normal ejaculation. Subjects and methods: This study was a cross-sectional, observational, non-interventional, epidemiological study, conducted from February 2012 to February 2013. Randomly selected married males were asked to answer two questionnaires in a direct interview. The first questionnaire assessed the PE complaint, the time between ejaculation and intromission (actual intravaginal ejaculatory latency time [IELT-a]), and the perceived normal average time between intromission and ejaculation (IELT-p). The second questionnaire used was the Arabic Index of Premature Ejaculation (AIPE). Results: A total of 3042 subjects were included. The mean (SD) age was 37.09 (9.1) years. The prevalence of PE in Qatar using the self-report and AIPE score was 38.5% and 36.2%, respectively. The median (interquartile range) IELT-a and IELT-p were 5 (3–13.5) and 15 (5–15) min. In the AIPE-confirmed PE group, and according to the AIPE severity classification, the differences in IELT-a and IELT-p between the severity groups were highly significant, with the duration of both IELT-a and ILET-p being higher in AIPE-No-PE and mild-PE groups ( P < 0.001 for both). A negative correlation was found between AIPE score and age in the PE group. Conclusion: The prevalence of PE in Qatar is high. PE prevalence was found to increase with age. The IELT and perception of normal IELT were both correlated with the severity of PE.